2021
DOI: 10.3389/fmed.2021.732042
|View full text |Cite
|
Sign up to set email alerts
|

Tangshen Formula Improves Diabetes-Associated Myocardial Fibrosis by Inhibiting TGF-β/Smads and Wnt/β-Catenin Pathways

Abstract: Cardiovascular disease has become the main cause of death among complications of diabetes. Myocardial fibrosis is a crucial pathological change of cardiovascular disease. Tangshen Formula (TSF) shows a good clinical effect in the treatment of diabetic kidney disease (DKD). However, whether TSF alleviates diabetes-associated myocardial fibrosis is still unknown. In the present research, we studied the effect and mechanism of TSF in the treatment of myocardial fibrosis in vivo and in vitro. We found that TSF tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This may alleviate myocardial fibrosis in KKAy mouse models by inhibiting TGF-β/Smad and Wnt/β-catenin signaling pathways. These findings may increase our knowledge regarding effect of TSF in diabetes (L. Hu, Wang, et al, 2021).…”
Section: Role Of Wnt In Type 2 Diabetesmentioning
confidence: 62%
“…This may alleviate myocardial fibrosis in KKAy mouse models by inhibiting TGF-β/Smad and Wnt/β-catenin signaling pathways. These findings may increase our knowledge regarding effect of TSF in diabetes (L. Hu, Wang, et al, 2021).…”
Section: Role Of Wnt In Type 2 Diabetesmentioning
confidence: 62%
“…Smad2/3 and Smad4 are downstream factors of the TGF-β/Smads signal pathway, followed by the stimulation of HG or TGF-β, Smad4 will bind to the phosphorylated Smad2/3 to form a complex and then translocated to the nucleus as transcriptional factors to promote the expression of ECM and inhibition of TGF-β/Smads signal pathway could alleviate excess ECM expression and improve DN (Hu et al. 2021 ). Consistent with these studies, our work indicated that kirenol could inhibit the TGF-β/Smads signal pathway and then alleviate ECM accumulation both in DN animal and cell models.…”
Section: Discussionmentioning
confidence: 99%
“…[110] The Tangshen formula has significant therapeutic effects on multiple organ damage, [111] including the treatment of fatty liver, [109] improvement of gastrointestinal dynamics, [112] and reduction of myocardial fibrosis while fighting renal fibrosis. [113]…”
Section: Advantages and Advances In Mechanism Ofmentioning
confidence: 99%